2018
DOI: 10.3389/fnins.2018.00592
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Sequencing of Alzheimer Disease Genes in African Americans Implicates Novel Risk Variants

Abstract: The genetic architecture of late-onset Alzheimer disease (AD) in African Americans (AAs) differs from that in persons of European ancestry. In addition to APOE, genome-wide association studies (GWASs) of AD in AA samples have implicated ABCA7, COBL, and SLC10A2 as AA-AD risk genes. Previously, we identified by whole exome sequencing a small number of AA AD cases and subsequent genotyping in a large AA sample of AD cases and controls association of AD risk with a pair of rare missense variants in AKAP9. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 43 publications
0
26
1
Order By: Relevance
“…These sample sizes are realistic in that they reflect the scales of recent deep sequencing studies in African Americans. For example, 489 Alzheimer’s cases and 472 controls were sequenced a target sequencing study on Alzheimer’s disease 51 . The Jackson Heart Study 52 has deeply sequenced more than 3400 African Americans.…”
Section: Simulation Designsmentioning
confidence: 99%
“…These sample sizes are realistic in that they reflect the scales of recent deep sequencing studies in African Americans. For example, 489 Alzheimer’s cases and 472 controls were sequenced a target sequencing study on Alzheimer’s disease 51 . The Jackson Heart Study 52 has deeply sequenced more than 3400 African Americans.…”
Section: Simulation Designsmentioning
confidence: 99%
“…An independent African American case–control study, however, could not replicate the association, with a carrier frequency of 9.2% in patients and 7.4% in controls. Differences in cohort ancestry between studies could be a potential explanation for this discrepancy [76].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous independent studies reported this observation in 2015, including hypothesis-free studies such as a large-scale imputation study [77] and a small exome-array association study [78], as well as targeted gene resequencing studies [71, 79]. Particularly rare PTC variants, comprising frameshift variants, nonsense variants, and variants causing out-of-frame splicing, were highly enriched in AD [80, 81, 75, 71, 82, 83, 72, 76, 8486, 77, 79].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To clarify these possibilities, it is necessary to deeply sequence the regulatory regions for a better understanding of the SLC6A3 genetic structure including the 3’ VNTRs, given the implications of SLC6A3 in a spectrum of diseases and other behavioral characteristics. This task requires systemic discovery of polymorphisms and haplotypes in the regulatory regions, through targeted deep-sequencing that is helpful in discovery of novel functional loci or mutations in different fields[6269]. In other words, the presence of multiple SLC6A3 regulatory regions mandates mechanistic studies of the SLC6A3 genetics, to help delineating functionally distinct SLC6A3 haplotypes.…”
Section: Introductionmentioning
confidence: 99%